2021
DOI: 10.1007/978-3-030-80421-3_13
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of a Meaningful Discovery Learning Support System for Supporting E-book User in Pair Learning

Abstract: In this paper, an experiment was conducted to study the learning performance when learning new knowledge in groups with an e-book system and a meaningful discovery learning support environment. The participants studied target new knowledge with an e-book in pairs; at first, all the knowledge points that appear in the e-book were displayed and learners in each pair were encouraged to actively create relations between the knowledge concepts together; after completing the task, they can compare their learner-gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…The next 5 statements in Table 4 were about the implementation of Discovery Learning model. Group activities through discovery learning is useful to improve students learning performance [22]. In this study, students found that group activity helped them easier to found ideas (Table 4).…”
Section: Agreementioning
confidence: 68%
“…The next 5 statements in Table 4 were about the implementation of Discovery Learning model. Group activities through discovery learning is useful to improve students learning performance [22]. In this study, students found that group activity helped them easier to found ideas (Table 4).…”
Section: Agreementioning
confidence: 68%